Exercise-induced PV network plasticity in the prelimbic cortex regulates the expression of fear memory in male mice - Neng-Yuan Hu; Xin Heng; Hao Li; Lang Huang; Yuan-Yue Dou; Yi-Hua Chen (Translational Psychiatry)
Abstract Many psychiatric disorders, such as anxiety disorders, are characterized by abnormal processing of fear-related information. Parvalbumin (PV) neurons in the prelimbic cortex (PL) are critically involved in fear expression. However, the role of plasticity of the local PV neuron network in the regulation of remote fear memory remains unknown. In this study, we showed that the retrieval of both recent and remote fear memory induced the high-PV plasticity in the PL. Acute chemogenetic inhibition of PV neurons in the PL decreased recent fear memory retrieval and suppressed the fear-induced shift toward high-PV neurons, while these effects were not observed three weeks after chemogenetic inhibition. On the other hand, chronic inhibition of these neurons led to a sustained reduction in fear memory retrieval and persistent suppression of fear-induced high-PV plasticity. Notably, voluntary running mimicked the effects of chronic inhibition of PV neurons and decreased the expression of fear memory, which could be blocked by chemogenetic activation of PV neurons. Together, these findings indicate an essential role for PV network plasticity in the PL in regulating fear memory expression and provide alternative methods for the treatment of certain anxiety disorders.